Public Memory and Cultural Trauma - Tota, Anna Lisa (Javnost-The Public, 2006)
The essay reviews following books: Jeffrey C. Alexander, Ron Eyerman, Bernhard Giesen, Neil J. Smelser, and Piotr Sztompka: Cultural Trauma and Collective Identity. Berkeley: University of California Press, 2004; Kendall R. Phillips (ur.): Framing Public Memory. Tuscaloosa: The University of Alabama Press, 2004.